Last order effect in altruistic loaning decision making via Kiva platform - Chia, Adena (Nanyang Technological University, 2023)
Order effect arises when subjects do not make a rational decision due to the order in which choices are presented. This study attempts to address potential concerns in previous research and extends the literature by examining last order effect in altruistic loaning decision- making using a crowdfunding platform called Kiva. Subjects were tasked as loaners and loaners’ decisions were subjected to the randomized order of borrowers. Our findings are empirically examined and indicate a significant relationship between the binary decision and the order effect. This suggests that borrowers placed in the later orders had a higher probability of being picked by loaners, indicating the inherent last order effect. Lastly, we further discuss the potential implications of last order effect in the real world.